The Severe Maternal Morbidity in the Kisanga Health Zone in Lubumbashi, South of the Democratic Republic of Congo - Chola, Joseph Mwansa; Belrhiti, Zakaria; Dieudonné, Mpunga Mukendi; Charles, Kaya Mulumbati; Herman, Tamubango Kitoko; Didier, Chuyi Kalombola; Mildred, Chola Chembo; Faustin, Chenge Mukelenge; Albert, Mwembo Tambwe (Jour Med Resh and Health Sci, 2022)
ABSTRACT While maternal death has traditionally been the primary indicator of maternal outcomes, the prevalence of severe pregnancy complications - or severe maternal morbidities - can provide a more complete picture of maternal and perinatal health issues when considered in conjunction with maternal deaths. The objectives of this work were to determine the prevalence of severe maternal morbidity, the socio-demographic characteristics of the patients, the conditions of admission and care as well as maternal and perinatal outcomes. All women with severe maternal morbidity during 4 months of a descriptive cross-sectional study with prospective harvest in the health zone of Kisanga in Lubumbashi were included in the study. These included cases of anemia, obstructed labor, hemorrhage, infections and high blood pressure. About one patient on ten received in maternity hospitals in Lubumbashi presented with severe maternal morbidity. Genital haemorrhages (44.6%), gestational hypertension (30.9%) and obstructed labor (14.4%) accounted for nearly 90% of the causes of severe maternal morbidity. Only three percent of the patients had access to a blood bank, 30% of the patients could have the opinion of a Obstetrician-Obstetrician and only one in five patients remained in intensive care if necessary. The patients were young, married for most, coming from a semi-urban environment with a low socio-economic level. No patient in this series had used the ambulance to get to the maternity ward. Maternal and perinatal mortality were 859 per 100,000 live births and 50 per 1,000 live births, respectively.The prevention and management of severe maternal morbidities requires an efficient and fully functional health system. Keywords: Severe maternal morbidity, efficient health system, Lubumbashi, DRC